Black performance on the outskirts of the left : a history of the impossible - Gaines, Malik (Sexual cultures., 2017)
This book illustrates the black political ideas that radicalized the artistic endeavors of musicians, playwrights, and actors beginning in the 1960s. These ideas paved the way for imaginative models for social transformation through performance. Using the notion of excess its transgression, multiplicity, and ambivalence Malik Gaines considers how performances of that era circulated a black political discourse capable of unsettling commonplace understandings of race, gender, and sexuality. Following the transnational route forged by W.E.B. Du Bois, Josephine Baker, and other modern political actors, from the United States to West Africa, Europe and back, this book considers how artists negotiated at once the local, national, and diasporic frames through which race has been represented. Looking broadly at performances found in music, theater, film, and everyday life from American singer and pianist Nina Simone, Ghanaian playwrights Efua Sutherland and Ama Ata Aidoo, Afro-German actor Gunther Kaufmann, to California-based performer Sylvester Gaines explores how shared signs of racial legacy and resistance politics are articulated with regional distinction. Bringing the lens forward through contemporary art performance at the 2015 Venice Biennial, Gaines connects the idea of sixties radicality to today s interest in that history, explores the aspects of those politics that are lost in translation, and highlights the black expressive strategies that have maintained potent energy.